Relationship between number of menopausal symptoms and work performance in Japanese working women. Issue 2 (February 2021) - Hashimoto, Keiko; Yoshida, Mikako; Nakamura, Yasuka; Takeishi, Yoko; Yoshizawa, Toyoko
Abstract: Objective: The presence of various menopausal symptoms could decrease work performance because symptom management strategies differ, and it is difficult to control all symptoms at work. The aim of this study was to examine the relationship between the number of menopausal symptoms experienced and work performance in working women. Methods: An online cross-sectional study was conducted with 599 working Japanese women aged 45 to 65 years. To represent work performance, absolute presenteeism was measured using the Japanese version of the World Health Organization and Work Performance Questionnaire short form, and menopausal symptoms were measured using the Greene Climacteric Scale. The total number of subscales on which a participant scored more than one point represented the number of menopausal symptoms. Results: Participants' mean age was 54.2 years, and 60.6% were postmenopausal. Their mean Greene Climacteric Scale score and mean absolute presenteeism score were 10.5 ± 10.6 and 61.7 ± 17.9, respectively. The proportions of participants who provided care for a family member, who had chronic disease, and who undertook regular exercise were significantly different among the four groups. After adjusting for other factors, absolute presenteeism was negatively correlated with the number of menopausal symptoms experienced (β = −0.13, P  < 0.001). Conclusions: Higher numbers of menopausal symptoms were correlated with lower work performance. The maintenance of health and the provision of appropriate working environments would help working women and improve work performance by reducing menopausal symptoms.